Psychosocial and Healthcare Experiences of OEF/OIF Veterans Before Suicide: Qualitative Analysis of VA Medical Records. (2nd January 2017) - Denneson, Lauren M.; Williams, Holly B.; Jacobson, Laura E.; Nguyen, Dan; Dobscha, Steven K.
ABSTRACT: To identify priority areas for future research, this study describes the psychosocial and healthcare experiences of 38 Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF) veterans before suicide. This analysis included veterans from 11 states who died by suicide and received Veterans Affairs healthcare in the 6 months before death. Findings revealed instances of under- or untreated mental health conditions, care coordination difficulties, and polypharmacy, and indicated the importance of examining military-related trauma and aggression, basic needs satisfaction, and treatment engagement in this veteran cohort.